Evaluation of EGFR and COX pathway inhibition in human colon organoids of serrated polyposis and other hereditary cancer syndromes - Priyanka Kanth; Mark W. Hazel; John C. Schell; Jared Rutter; Ruoxin Yao; Alyssa P. Mills; Don A. Delker (Familial Cancer, 2024)
Serrated polyposis syndrome (SPS) presents with multiple sessile serrated lesions (SSL) in the large intestine and confers increased colorectal cancer (CRC) risk. However, the etiology of SPS is not known. SSL-derived organoids have not been previously studied but may help provide insights into SPS pathogenesis and identify novel biomarkers and chemopreventive strategies. This study examined effects of EGFR and COX pathway inhibition in organoid cultures derived from uninvolved colon and polyps of SPS patients. We also compared with organoids representing the hereditary gastrointestinal syndromes, Familial Adenomatous Polyposis (FAP) and Lynch syndrome (LS). Eighteen total organoid colon cultures were generated from uninvolved colon and polyps in SPS, FAP, LS, and non-syndromic screening colonoscopy patients. BRAF and KRAS mutation status was determined for each culture. Erlotinib (EGFR inhibitor) and sulindac (COX inhibitor) were applied individually and in combination. A 44-target gene custom mRNA panel (including WNT and COX pathway genes) and a 798-gene microRNA gene panel were used to quantitate organoid RNA expression by NanoString analysis. Erlotinib treatment significantly decreased levels of mRNAs associated with WNT and MAPK kinase signaling in organoids from uninvolved colon from all four patient categories and from all SSL and adenomatous polyps. Sulindac did not change the mRNA profile in any culture. Our findings suggest that EGFR inhibitors may contribute to the chemopreventive treatment of SSLs. These findings may also facilitate clinical trial design using these agents in SPS patients. Differentially expressed genes identified in our study ( MYC, FOSL1 , EGR1, IL33, LGR5 and FOXQ1 ) may be used to identify other new molecular targets for chemoprevention of SSLs.

A community-level sampling method for detection of Meloidogyne enterolobii and other root-knot nematodes in sweetpotato storage roots - Julianna Culbreath; Catherine Wram; Churamani Khanal; Tyler Bechtel; Phillip A. Wadl; John Mueller; William B. Rutter (Crop Protection, 2023)

Correction to: Anthropogenic factors influence the occupancy of an invasive carnivore in a suburban preserve system - John P. Vanek; Andrew U. Rutter; Timothy S. Preuss; Holly P. Jones; Gary A. Glowacki (Urban Ecosystems, 2021)

Anthropogenic factors influence the occupancy of an invasive carnivore in a suburban preserve system - John P. Vanek; Andrew U. Rutter; Timothy S. Preuss; Holly P. Jones; Gary A. Glowacki (Urban Ecosystems, 2021)

Blood lipids and colorectal polyps: testing an etiologic hypothesis using phenotypic measurements and Mendelian randomization - Michael N. Passarelli; Polly A. Newcomb; Karen W. Makar; Andrea N. Burnett-Hartman; John D. Potter; Melissa P. Upton; Lee-Ching Zhu; Michael E. Rosenfeld; Stephen M. Schwartz; Carolyn M. Rutter (Cancer Causes & Control, 2015)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Adverse events after screening and follow-up colonoscopy - Carolyn M. Rutter; Eric Johnson; Diana L. Miglioretti; Margaret T. Mandelson; John Inadomi; Diana S. M. Buist (Cancer Causes & Control, 2012)

β-Ketoacyl-acyl carrier protein synthase III from pea (Pisum sativum L.): properties, inhibition by a novel thiolactomycin analogue and isolation of a cDNA clone encoding the enzyme - Lesley A. Jones; Andy M. Gane; Derek Herbert; David L. Willey; Andrew J. Rutter; Peter Kille; Jane E. Dancer; John L. Harwood (Planta, 2003)

Movement ofMycosphaerella fijiensis spores and sigatoka disease development on plantain close to an inoculum source - John Rutter; Peter J. A. Burt; Fernando Ramirez (Aerobiologia, 1998)

Airborne spore loads and mesoscale dispersal of the fungal pathogens causing Sigatoka diseases in banana and plantain - Peter J. A. Burt; John Rutter; Fernando Ramirez (Aerobiologia, 1998)